Centralized management IoT Platform (IoT Central Hub) - Rodrigues, António dos Santos (2021)
On information technology topics, the word innovation is increasingly present every day. Regarding Internet of Things (IoT) technology subject, it’s not different. Every year new IoT products and services are created and presented that allow users to make their lives easier and simpler, connecting people to devices remotely and automatically, generating mobility and operability of technology services through the heterogeneity of devices connected to the internet. Based on this obstacle found in daily home technology users, this thesis works to develop the study of the development of a unique and easy use platform. On this platform, it is possible to have IoT devices centralized on the same local network unit so that they can be managed and manipulated through a simple and intuitive graphical interface. Thus, management is unified and practical for any type of user who is interested in using this technology. In this thesis, good practices and the best solutions researched within the practice of IoT management were studied in different scenarios. Covering types of technologies, proposed architectures, configuration processes and compatibility analysis of features and functionality of different devices currently on the market. Thus, this work aims to present in detail the study of the prototype of a unified platform that allows configuring, monitoring and managing the integration between heterogeneous devices currently on the market for residential users.